Revision of the New World cycad weevils of the subtribe Allocorynina, with description of two new genera and three new subgenera (Coleoptera: Belidae: Oxycoryninae) - O’brien, Charles W.; Tang, William (Zootaxa, 2015)
The taxonomy of the weevils inhabiting male cycad cones in the New World is reviewed. All species belong in a single subtribe, Allocorynina, of the family Belidae, subfamily Oxycoryninae and tribe Oxycorynini and are known to develop only in cones of the cycad genera Dioon and Zamia. Most species of Rhopalotria Chevrolat develop in male cones of Zamia ranging from Mexico, Belize, the Caribbean (Cuba, Isle of Youth, Cayman Islands, Jamaica and the Bahamas) to southern Florida, and one species in those of Dioon spinulosum in Mexico. Rhopalotria consists of three previously described species, two previously described genus-group names (treated herein as subgenera) and four new species described herein: subgenus Allocorynus Sharp with R. calonjei n. sp., R. furfuracea n. sp., R. mollis (Sharp) and R. vovidesi n. sp., and the nominate subgenus Rhopalotria with R. dimidiata Chevrolat, R. meerowi n. sp. and R. slossoni (Schaeffer). The species of Parallocorynus Voss develop only in cones of Dioon in Mexico, and the genus consists of one previously described species, the nominate subgenus and three new subgenera and 11 new species described herein: subgenus Dysicorynus n. subg. with P. andrewsi n. sp. and P. sonorensis n. sp., subgenus Eocorynus n. subg. with P. chemnicki n. sp. and P. schiblii n. sp., subgenus Neocorynus n. subg. with P. iglesiasi n. sp. and P. inexpectatus n. sp., and the nominate subgenus Parallocorynus with P. bicolor (Voss), P. gregoryi n. sp., P. jonesi n. sp., P. norstogi n. sp., P. perezfarrerai n. sp. and P. salasae n. sp. Two new genera are described, Protocorynus with one new species in Honduras, P. bontai, and Notorhopalotria with four new species ranging from Costa Rica to Colombia, N. montgomeryensis, N. panamensis, N. platysoma and N. taylori. Keys to genera, subgenera and species are provided. All of these weevils are believed to be involved in pollination of their host cycads.